The relationship between perceived learning, academic performance and academic engagement in virtual education for university students - (:unkn) unknown (Asian Online Journal Publishing Group, 2024)
This study aimed to determine whether the three dimensions of academic engagement (cognitive, emotional and behavioral) were positively associated with perceived learning and academic performance. The participants were 301 university students from Lima. ...
Keywords: Educación virtual; Rendimiento académico